UNEARTHLY : integrating motion capture into a stylised 3D film - Leng, Carol Jia Yin (Nanyang Technological University, 2020)
Although the market for motion capture has been growing steadily in the live-action CG and game industry, motion capture remains largely underused in stylised films due to the realistic nature of the data captured. This report will elaborate on the processes and workflow on breaking past these limitations to successfully incorporate motion capture into a semi-realistic, stylised 3D animation, such as UNEARTHLY.